Pembuatan dan Karaterisasi Tablet NPN Lepas Lambat Berlapis Polikaprolakton Sebagai Suplement Ruminansia - Edtyva Monicha; Akmal Djamaan; Rini Agustin; Rusmana Wijaya Setia Ningrat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Productivity of ruminant cattle can be increased by providing non-protein nitrogen, especially urea. Urea not only has benefits as a plant fertilizer, but is also used as a substitute for nitrogen sources for ruminants. The purpose of this research is to use urea more efficiently because urea in the rumen is degraded more quickly to form ammonia so that urea excretion becomes faster in the urine. In this study it was designed so that urea is released in a slow release, its use is more practical and the dosage is correct. The method used is to make urea tablets and then coat them with a coating, characterize the tablets including their shape and urea content, then test the release of the tablets in vitro in rumen fluid. Based on this, the characteristics of the tablets are using Scanning electron microscopy (SEM), Differential Scanning Calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR) methods. From the results of the study showed that urea tablets fulfilled the tablet evaluation including tests for uniformity in size, weight variation, tablet hardness and friability. Meanwhile, for testing the release of urea tablets in the rumen fluid, it can be seen from testing that 70% of the urea tablets without coating were released, while for the coated urea tablets, only 15% were released in the first minute. Sequentially the release of urea tablets from the first minute with three successive repetitions of the test was 14.641; 15.323 and 14.798 %. Meanwhile, tablets that were not coated in the first minute released as much as 71.257%. For this reason, the manufacture of polycaprolactone-coated slow release urea tablets makes urea more beneficial for ruminants without rapid excretion and lasts longer in the rumen so that rumen microbes take advantage of this nitrogen source to form microbial protein.